Unions’ Conceptualizations of Members’ Professional Interests and Influence in the Workplace - Bie-Drivdal, Arnhild (Nordic Journal of Working Life Studies, 2020)
The role of unions as agents of professional knowledge is seldom addressed in studies on working life relations.This article investigates how unions with different degrees of professionalization con- ceptualize members’ interests and influence in the workplace. Two unions of professionals and one general union in the Norwegian public sector are compared. The data consist of union documents, speeches, and interviews with 12 workplace representatives. A ‘union logic’ and ‘professional association logic’ are developed and applied as analytical ideal types, and the unions’ conceptualizations and combinations of these institutional logics are analyzed. The article finds similarities and differences between the unions and interesting differences between the unions’ micro and macro levels. Further, a distinct hybrid logic is identified as a ‘union of professionals logic’, with professional influence and the agency of elected representatives as key aspects. Introducing perspectives from the study of professions, the article contributes to a reconceptualization of the study of unions within the Nordic model – and beyond.